Microglia and neurons in the hippocampus of migratory sandpipers. - Diniz, C G; Magalhães, N G M; Sousa, A A; Santos Filho, C; Diniz, D G; Lima, C M; Oliveira, M A; Paulo, D C; Pereira, P D C; Sherry, D F; Picanço-Diniz, C W (Brazilian Journal of Medical and Biological Research, 2016)
The semipalmated sandpiper Calidris pusilla and the spotted sandpiper Actitis macularia are long- and short-distance migrants, respectively. C. pusilla breeds in the sub-arctic and mid-arctic tundra of Canada and Alaska and winters on the north and east coasts of South America. A. macularia breeds in a broad distribution across most of North America from the treeline to the southern United States. It winters in the southern United States, and Central and South America. The autumn migration route of C. pusilla includes a non-stop flight over the Atlantic Ocean, whereas autumn route of A. macularia is largely over land. Because of this difference in their migratory paths and the visuo-spatial recognition tasks involved, we hypothesized that hippocampal volume and neuronal and glial numbers would differ between these two species. A. macularia did not differ from C. pusilla in the total number of hippocampal neurons, but the species had a larger hippocampal formation and more hippocampal microglia. It remains to be investigated whether these differences indicate interspecies differences or neural specializations associated with different strategies of orientation and navigation.